The potential effect of coconut water as natural healer in adult patient with chronic periodontitis: A preliminary clinical study - Abllah, Zurainie; Syed Ibrahim, Syarifah Nurul Afifah; Rahaman, Hamiza; Yaacob, Munirah; Dewi Ardini, Yunita (2019)
Introduction: Mechanical and chemical debridement had been practiced as one of the management for chronic periodontitis. The main objectives of this study was to investigate the clinical effect of coconut water when used topically in reducing periodontal pocket, inflammation and bleeding on probing in chronic periodontitis patients after mechanical debridement. Materials and methods: Randomized control study was chosen as study design in this research project. 12 patients who have moderate to severe chronic periodontitis were selected from patients whom attended Polyclinic Kulliyyah of Dentistry, IIUM Kuantan Campus from November 2016 to January 2018. The subjects were divided into 2 groups after randomization done; Intervention Group and Control Group. All patients had undergone ultrasonic scaling and root planning by using hand instruments. 6 patients in Intervention Group were given fresh coconut water to drink during daytime. The first re-assessment was done after 6 weeks. The control group of another 6 patients didn’t receive any medicament. Paired sample t-test was used to analyse the pre and post intervention data. Results: Probing depth (PD) at mid-buccal site and bleeding on probing (BoP) shown significant result (P<0.05) in intervention group after 6 weeks while in control group there was no significant improvement. Conclusion: Coconut water has potential benefit in reducing the periodontal pockets and reducing the inflammation in chronic periodontitis.